A guillotine amputation at the ankle level—how to quickly remove a septic foot: a case report. (1st September 2021) - Ho, Kristie; Arias, Sandra; Roshan, Donald; Dishner, Katie; Lardizabal, Marisse; Roth, Bryan; Matthews, Marc R
Abstract : As of 2014, diabetes is estimated to affect 422 million people globally. It is well recognised that lower extremity amputations secondary to diabetes have a high mortality rate perioperatively. The purpose of this article is to provide a simple, step-by-step guide to surgeons who need to perform a transtibial amputation. The case report of a 62-year-old female patient with poorly controlled diabetes who developed necrotising fasciitis of the lower extremity and systemic sepsis is used to illustrate the procedure. Knowing how to complete this operation is essential due to its effectiveness in quickly eliminating a source of pedal sepsis.